2010
DOI: 10.17221/30/2010-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cadmium on growth and antioxidant responses in Glycyrrhiza uralensis seedlings

Abstract: In the present study, Glycyrrhiza uralensis (Leguminosae) seeds were germinated and grown with different concentrations (0, 0.05, 0.1, 0.2 and 0.4 mmol/l) of cadmium acetate, in order to investigate the effects of cadmium on the growth, uptake, superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), polyphenol oxidase (PPO) and phenylalanine ammonia-lyase (PAL) activities in Glycyrrhiza uralensis seedlings. Uptake of Cd in different tissues of seedlings increased with increasing Cd concentrations in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 27 publications
7
16
1
1
Order By: Relevance
“…The maximum amount of Cd was found in roots rather than stems and leaves of Brassica juncea. Our results contrast with those of Zheng et al, (2010) who reported that normally cadmium ions are mainly retained in the roots and only small amounts are transported to the shoots. Roots of the plant act as a barrier against heavy metal translocation and this may be a potential tolerance mechanism operating in the roots (Bonnet et al, 2010).…”
Section: Resultscontrasting
confidence: 99%
“…The maximum amount of Cd was found in roots rather than stems and leaves of Brassica juncea. Our results contrast with those of Zheng et al, (2010) who reported that normally cadmium ions are mainly retained in the roots and only small amounts are transported to the shoots. Roots of the plant act as a barrier against heavy metal translocation and this may be a potential tolerance mechanism operating in the roots (Bonnet et al, 2010).…”
Section: Resultscontrasting
confidence: 99%
“…These results are coincidence to the results of Dražić et al (2006) that reported Cd decreased root and shoot of alfalfa seedling and to the results of Li et al (2005). Growth reduction under Cd toxicity conditions was also observed for several species tested, including Cucumus sativus (Abu-Muriefah, 2008), Lemna polyrrhiza (John et al, 2008) and Glycyrrhiza uralensis (Zheng et al, 2010). However Cd decreased the germination speed and percentage but it doesn't have any significant effect on them.…”
Section: Discussionsupporting
confidence: 88%
“…At higher concentration of Pb, the SOD decreased significantly in water hyacinth [45]. In other plants, varying changes in SOD and POD activities were observed in response to heavy metal stress [18,41,42,45,50,54,55]. An increase in the activities of the antioxidative enzyme (SOD and POD) under heavy metal stress could be attributed to the tolerance of heavy metals in plants.…”
Section: Discussionmentioning
confidence: 95%